Effect of Specific Energy Input on Cyanide Reduction in Jack Bean (Canavalia ensiformis L.) Flour Treated with High Pulsed Electric Field - Maulidva Suci Rahmawati; Budi Hariono (P3M Politeknik Negeri Jember, 2026)
Jack bean (Canavalia ensiformis L.) is a potential source of plant-baes protein; however, its utilization is limited by the presence of cyanogenic compounds that release hydrogen cyanide (HCN), which is toxic. Conventional thermal detoxification methods are effective but may cause nutritional degradation and require extended processing time. High Pulsed Electric Field (HPEF) is a non-thermal technology that induces electroporation. Increasing cell membrane permeability and facilitating the release of intracellular compounds without high-temperature treatment. This study aimed to evaluate the effect of HPEF treatment with varying specific energy inputs on HCN content in jack bean flour and to determine the treatment that achieved the highest HCN reduction. Three treatment were applied: control (P1), HPEF at 30 kV/cm with specific energy 1,3 kJ/kg (P2), and HPEF at 10 kV/cm with specific energy 3,5 kJ/kg (P3). HCN content was determined using the steam distillation method. Data were analyzed using one-way ANOVA followed by the Games-Howell pos-hoc test at a 95% confidence level. Results showed that HPEF treatment significantly reduced HCN content compared to the control (p<0,05). HCN levels decreased from 146,90 ppm in P1 to 103,30 ppm in P2 and 88,70 ppm in P3. Although P3 applied lower electric field strength than P2, its higher specific energy input resulted in greater HCN reduction, indicating that specific energy input is a more determinative parameter than electric field strength alone in characterizing HPEF treatment intensity. However, all final HCN levels remained substantially above the permissible food safety threshold of 10 ppm, indicating that HPEF at the parameters applied in this study is not yet sufficient as a standalone detoxification method. These finding suggest that HPEF has potential as a non-thermal pretreatment approach for HCN reduction in jack bean flour, with further optimization of specific energy input required to meet food safety standards.